Ethical and Bioethical Dilemmas in Paediatric Primary Health Care Setting - José Jesús García Mendiola; Gisselle Chi Gil; Maite Piñeiro Barreiro; Niurka Tamara Callejas Sánchez (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2011)
Medical Ethics gathers a group of principles and standards that rule out the behaviour amongst the health staff and amongst the doctor-patient and doctor-relatives relationship in order to preserve the patient's health, treatment and rehabilitation. Bioethics has its bases on society in the health-patient team, and decisions can be taken by an Ethics Commission with the patient's participation in the decision-taking process. The paediatrician in the primary health care setting should give a qualified health attention not only to the children but to their family members too due to the specialists' commitment with the Cuban public health in general. Therefore, this bibliographical review is carried out to reflect on the main ethical dilemmas at the primary health care setting in the paediatric practice.